Simulating maize yield in sub‑tropical conditions of southern Brazil using Glam model - Bergamaschi, Homero; da Costa, Simone Marilene Sievert; Wheeler, Timothy Robert; Challinor, Andrew Juan (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the feasibility of simulating maize yield in a sub‑tropical region of southern Brazil using the general large area model (Glam). A 16‑year time series of daily weather data were used. The model was adjusted and tested as an alternative for simulating maize yield at small and large spatial scales. Simulated and observed grain yields were highly correlated (r above 0.8; p
Keywords: Zea mays; crop modeling; crop parameters; crop‑weather relationships.